Electroplating of copper for application in sub-0.25 micron device manufacturing - Seah, Chin Hwee. (2009)
An in-depth study of the copper electroplating process was carried out with different process parameters such as seed materials, current densities and electrolytes in order to fabricate nanocrystalline electroplated copper to fill up the line and via trenches in sub-0.25 urn devices. The effect of annealing on the morphology and properties of the electroplated copper was also investigated.